A novel role for CCL3 (MIP-1α) in myeloma-induced bone disease via osteocalcin downregulation and inhibition of osteoblast function - Vallet, Sonia; Pozzi, S.; Patel, K.; Vaghela, N.; Fulciniti, M. T.; Veiby, P.; Hideshima, T.; Santo, L.; Cirstea, D.; Scadden, D. T.; Anderson, K. C.; Raje, N. (Leukemia, 2011)
Upregulation of cytokines and chemokines is a frequent finding in multiple myeloma (MM). CCL3 (also known as MIP-1α) is a pro-inflammatory chemokine, levels of which in the MM microenvironment correlate with osteolytic lesions and tumor burden. CCL3 and its receptors, CCR1 and CCR5, contribute to the development of bone disease in MM by supporting tumor growth and regulating osteoclast (OC) differentiation. In this study, we identify inhibition of osteoblast (OB) function as an additional pathogenic mechanism in CCL3-induced bone disease. MM-derived and exogenous CCL3 represses mineralization and osteocalcin production by primary human bone marrow stromal cells and HS27A cells. Our results suggest that CCL3 effects on OBs are mediated by ERK activation and subsequent downregulation of the osteogenic transcription factor osterix. CCR1 inhibition reduced ERK phosphorylation and restored both osterix and osteocalcin expression in the presence of CCL3. Finally, treating SCID-hu mice with a small molecule CCR1 inhibitor suggests an upregulation of osteocalcin expression along with OC downregulation. Our results show that CCL3, in addition to its known catabolic activity, reduces bone formation by inhibiting OB function, and therefore contributes to OB/OC uncoupling in MM.